“PENGARUH PEMBERIAN MIKORIZA ARBUSKULA DAN PUPUK ORGANIK TERHADAP PERTUMBUHAN BIBIT JATI PUTIH (Gmelina arborea Roxb.)” - Anugrah Condro Santoso; Tri - Harwati; Siswadi - - (Innofarm:Jurnal Inovasi Pertanian, 2013)
Research on "The Effect of giving arbuscular mycorrhizal and Organic Fertilizer Against growth of white teak seedlings (Gmelina arborea Roxb.) has been started on April 2013 until July2013 at green house of agriculture faculty of Slamet Riyadi University which is located in Village Kadipiro,Subdistrict Banjarsari, Town Surakarta, Province Central Java. The research design  was factorial Completely Randomized Design (CRD) consisting of 2 factor and 3 replication. Data  were  analyzed  by  Analysis  of  Variance  (Anova),  continued  by  Honestly Significant Diferent Test (HSDT) on 5 % significant level. The results show: Mycorrhizal best dose is 10 g / polybag because it can produce the highest seedlings height is 157.89 cm, weight  of  the  fresh  seedlings is  333.42 g  toughest,  heaviest  and  dry  weightof seedlingsis 86.37 g,. Best organic fertilizer is compost because it can produce the highest seedlings height 13 cm, diameter of the largest trunk is 12.18 mm, the highest number of leaves is 30.33 leaves, fresh weight is 306.49 g toughest seedlings, and dry weight of seedlingsof the heaviest is 79,86 g., and Best interactions happen  on  a  combination  of  compost  with  mycorrhizal  dosage  10  g/polybag because  it  produces  the  smallest  root-shoot  ratio  is  2.116,  a  combination  of compost with mycorrhizal dosage of 15 g / polybag because it produces the smallest root-shoot ratio is 2.237, and the combination of mycorrhizal dose 10 g / polybag with cow dung manure because it produces the smallest root-shoot ratio is 2.175. Key words : arbuscular mycorrhizal, Organic Fertilizer, white teak